Rapid Destructive Arthropathy of the Knee in Parkinson's Disease with Pisa Syndrome: A Case of Knee-Spine Syndrome. (6th September 2021) - Takai, Hirokazu; Kitajima, Masato; Takai, Seiko; Takahashi, Tomoki; Katsura, Ken-ichi; Tokunaga, Makoto; Watanabe, Susumu
Abstract : The changes occurring in knee osteoarthritis often cause alterations in the spinal loading condition, which further lead to degenerative changes. This close relationship of the knee and spine has been reported as knee-spine syndrome. A 60-year-old woman with Parkinson's disease (PD; Hoehn-Yahr stage IV) had severe knee pain with moderate lateral osteoarthritis of the knee (Kellgren-Lawrence classification grade II). Conservative therapy had no effect at all, and the knee developed destructive osteoarthritis rapidly without any traumatic episodes. The radiographic findings progressed to Kellgren-Lawrence grade IV within a month. Magnetic resonance imaging revealed partial depression of the joint surface, including shredded ossicles and substantial amounts of synovial fluid. The imaging findings were considered to be caused by a subchondral insufficiency fracture (SIF). Total knee arthroplasty was performed using a semiconstrained prosthesis. The alignment of her lower extremity improved, and the patient could walk without knee pain. The patient had Pisa syndrome, a lateral flexion of the trunk, which is a postural deformity of the trunk secondary to long-standing PD. The postural deformity in PD is not based on spinal deformity itself but on the loss of postural reflexes and the imbalance of muscle tonus. Her left knee pain appeared 1 month after L1-L4 posterior lumbar interbody fusion (PLIF) as the Pisa syndrome to her left side worsened. The more the trunk tilts to the lateral side, the center of the gravity axis will shift and pass through more lateral points of the knee and result in higher knee load. The stress concentration from the spine to the lateral joint of the knee caused lateral knee osteoarthritis, namely, knee-spine syndrome. When patients undergo correction surgery for adult spinal disorder with impairment of postural reflexes, they need to be followed up carefully regarding not only the spinal alignment but also the lower extremities.